HAKIKAT, TUJUAN DAN FUNGSI EVALUASI DALAM PENGEMBANGAN PEMBELAJARAN - ., Suarga (Inspiratif Pendidikan, 2019)
The Nature of Evaluation is a "Handbook on formative and summative evaluation of student learning", which means Evaluation is gathering enough evidence to be used as a basis for determining whether there is a change in students. So, we as teachers must believe that education can bring change to students. Educational evaluation is very necessary in education, among others, providing information that is used as a basis for: 1. Making policy and decisions. 2. Assessing the results achieved by students. 3. Assess the curriculum. 4. Giving trust to the school. 5. Monitor the funds that have been given. 6. Improve education materials and programs. The evaluation results on the world of national education are quite alarming, not only in terms of quality but also failure in shaping the character of the nation's young generation. Education is the responsibility of all parties, where the goal of education is to humanize humans. Form high quality human resources.